Penelope and the Pirates - Young, James, 1956- (New York : Arcade Pub., 1990)
Follows the adventures of Penelope the cat as she foils a band of pirates and finds a fabulous buried treasure.
Keywords: Cats -- Fiction; Pirates -- Fiction; Buried treasure -- Fiction